The Brave New World Revealed: Wrestling with Reality, Rationing, and Rationality - Manthous, Constantine A.; White, Douglas B.; Carson, Shannon S. (Seminars in Respiratory and Critical Care Medicine, 2012)
When Dr. Joseph Lynch, editor of Seminars in Respiratory and Critical Care Medicine, invited us to organize and edit this topic we—and our contributors—were initially baffled about how we could marry outcomes, ethics, and economics. His perspective as an elder-statesman, who has observed the evolution of critical care medicine over 4 decades, provided perspective as to how these three areas are intimately related and that their synthesis is essential if the US medical system is to best serve our populace as resources become increasingly limited.
Keywords: ethics; disability; critical care; economics; justice; autonomy; informed consent; beneficence